Breast cancer etiologies among young Malay breast cancer patients - Sulaiman, Szariannie; Mohd Noor, Noor Azlan (UPM Press, 2020)
There is a widely held view that breast cancer etiologies vary among women of diverse social-cultural backgrounds. As such, this qualitative study aimed at identifying the various factors associated with the onset of breast cancer symptoms among young Malay women. Thirteen young Malay breast cancer patients in Kuala Lumpur and several selected areas of Selangor were selected through purposive snowballing technique. In relation to this, ethnographic fieldwork employing a qualitative approach was conducted for approximately 10 months. A series of in-depth interviews, phone and online interviews guided by a semistructured interview schedule and participant observation were carried out among the informants of this study. From the thematic analysis of the field notes, it is evident from the present study that young Malay informants had attributed their breast cancer illness to supernatural causes and non-supernatural causes. They strongly believed that saka, spirit attacks, lifestyles, unhealthy food consumption, and hazardous working environments could have contributed to the onset of their breast cancer symptoms. The findings of the present study are imperative particularly for health care providers to understand the health seeking behaviours of breast cancer patients in the provision of cancer control, particularly in diverse populations like Malaysia.